Sistem Pendukung Keputusan Pemilihan Mekanik Terbaik Dengan Metode Analytical Hierarchy Process - Badrul, Mohammad; Gultom, Ranita (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Human resources in a company organization are very important to support the progress and quality of the company in achieving its goals. Human resources are a determining factor for success in achieving a goal. Therefore, a way to improve employee performance is needed, namely by evaluating employee performance. CV. Karya Indah Motor is required to continue to strive to provide the best service to ensure quality, reliability, efficiency and satisfaction to users. To do all of that, the company must have a mechanic whose job is to serve customers who come to perform regular service. Currently there is an assessment process or selection of the best mechanic, but it tends to be subjective based on proximity to his superiors so that it will cause jealousy and eventually mechanics are less motivated to work. Therefore, an appropriate method is needed to calculate the weighting of the criteria used to produce a decision to determine the best mechanic. Analytical Hierarchy Process method can assist in determining the priority of several criteria by conducting a pairwise comparison analysis of each criterion. The criteria determined include discipline, attendance, SOP standards, loyalty, and responsibility. With a decision support system that provides information, modeling and data manipulation that is used to help decision makers in semi-structured situations.